2015
DOI: 10.1186/s13104-015-1008-0
|View full text |Cite
|
Sign up to set email alerts
|

Seniors’ perspectives on care: a case study of the Alex Seniors health clinic, Calgary

Abstract: BackgroundPrimary care initiatives face an imperative to not only reduce barriers to care for their patients but also to uniquely accommodate the complex needs of at-risk patient populations. Patient-centered multidisciplinary care team models for primary care, like the Alex Seniors Clinic, are one approach for providing comprehensive care for marginalized seniors. The purpose of this qualitative study was to explore patient perspectives on the responsiveness of the Alex Seniors Clinic to their stated health n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…From our review, there is considerable evidence that TBPCC can enhance patient experience of care through strategies related to accessibility, respectful supportive relationships, enhanced opportunities for knowledge sharing, self-management, and community advocacy (24,33,34,40). The availability of enhanced case management or specialized support roles also positively influences patient experience (44,45,72).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…From our review, there is considerable evidence that TBPCC can enhance patient experience of care through strategies related to accessibility, respectful supportive relationships, enhanced opportunities for knowledge sharing, self-management, and community advocacy (24,33,34,40). The availability of enhanced case management or specialized support roles also positively influences patient experience (44,45,72).…”
Section: Discussionmentioning
confidence: 95%
“…However, other studies suggest the accessibility of care is still an issue, even in highly-functioning team-based practices (33,43,46). A pan-Canadian study found that the likelihood of reporting access issues or unmet needs was not significantly different in TBC vs. non-TBC settings (68).…”
Section: Care Process and Qualitymentioning
confidence: 98%
See 3 more Smart Citations